Recent Advances in ROS-Sensitive Nano-Formulations for Atherosclerosis Applications - Ji, Hao; Peng, Renyi; Jin, Libo; Ma, Jiahui; Yang, Qinsi; Sun, Da; Wu, Wei (Pharmaceutics, 2021)
Over the past decade, ROS-sensitive formulations have been widely used in atherosclerosis applications such as ROS scavenging, drug delivery, gene delivery, and imaging. The intensified interest in ROS-sensitive formulations is attributed to their unique self-adaptive properties, involving the main molecular mechanisms of solubility switch and degradation under the pathological ROS differences in atherosclerosis. This review outlines the advances in the use of ROS-sensitive formulations in atherosclerosis applications during the past decade, especially highlighting the general design requirements in relation to biomedical functional performance.